IT Management in Policing: Main Advantages and Disadvantages of IT for Police Managers - Tosun, Hamza (European Scientific Journal, ESJ, 2016)
As a public organization, police agencies have placed various IT systems into service in order to achieve their goals. More especially, in community policing era, information technology have greatly assisted police managers to improve policing capabilities in terms of serving effectively and efficiently. In describing three dimensions of the IT Management, this paper explores the advantages and disadvantages of using IT in policing area. IT Management offers great advantages in policing for police managers. However, before initiating an IT project, police managers should consider their organizational capacity in terms of budget, personnel, and organizational structure.